2021
DOI: 10.1140/epjc/s10052-021-09037-4
|View full text |Cite
|
Sign up to set email alerts
|

The renormalised $$\mathrm{O}(a)$$ improved vector current in three-flavour lattice QCD with Wilson quarks

Abstract: We present the results of a non-perturbative determination of the improvement coefficient $$c_\mathrm{V}$$ c V and the renormalisation factor $$Z_\mathrm{V}$$ Z V , which define the renormalised vector current in three-flavour $$\mathrm{O}(a)$$ O ( … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 42 publications
(156 reference statements)
5
13
0
Order By: Relevance
“…2, these local estimators of Z do not exhibit plateau-like behaviour; this was also observed for a similar Ward identity adopted to compute the improvement coefficient of the vector current in Ref. [24]. Note, however, that this is not problematic; since Z is obtained from a Ward identity, its value at any time slice qualifies as a well-defined estimate.…”
Section: Renormalisation Constant Zsupporting
confidence: 61%
See 4 more Smart Citations
“…2, these local estimators of Z do not exhibit plateau-like behaviour; this was also observed for a similar Ward identity adopted to compute the improvement coefficient of the vector current in Ref. [24]. Note, however, that this is not problematic; since Z is obtained from a Ward identity, its value at any time slice qualifies as a well-defined estimate.…”
Section: Renormalisation Constant Zsupporting
confidence: 61%
“…In Ref. [24] it was explicitly shown that L is constant up to O(a) cut-off effects across the coupling range also considered in the present work. We thus expect our final results for r m and Z to only be affected by O(a 2 ) effects.…”
Section: Numerical Setupmentioning
confidence: 52%
See 3 more Smart Citations